Досвід культивування Cattleyopsis lindenii (Lindl.) Cgn. (Orchidaceae Juss.) - Ivannikov, R.V.; Kovalskaya, L.A.; Lavrentyeva, A.N. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
In the article the results of long-term observation of Cattleyopsis lindenii (Lindl.) Cgn. (Orchidaceae Juss.) plants development ex vitro and in vitro were summarized. The adaptation of plants received from their natural habitats under greenhouse conditions was completed successfully. The procedure of seed propagations of C. lindenii in vitro was elaborated. The methods of seedlings adaptation under greenhouse conditions were optimized.